Real-world quality of service (QoS) performance in Radio over Fiber (RoF) networks: experimental testbed - Mohamad, R.; Idrus, S. M.; Abuajwa, O.; Yusoff, Z.; Yaakob, S.; Ja'afar, P. N. (Academic Press I, 2025)
The Radio over Fibre (RoF) downlink system has been designed to coexist with the Passive Optical Network (PON) technology, utilising the wavelength division multiplexing (WDM) method to support fibre-to-the-home (FTTH) installations and deliver high-speed broadband services. The system performance must meet the standards set by the European Telecommunication Standard Institute (ETSI) and telecommunications service providers (TSP) requirements. In this paper, new RoF system is designed to complement the PON deployment based on developing optical line terminal-multipoint radio over fibre (OLT-MROF), Radio Access Unit (RAU), Outdoor Unit (ODU), and RoF broadband terminal unit (RoF-ROF-BTU) using the field programmable gate arrays (FPGA). Then, an experimental testbed on the RoF downlink system in a rural area is conducted to evaluate the quality of service (QoS) measurement for high-speed broadband services, including triple-play services (TPSs): data, voice, and video for Internet Protocol Television (IPTV) at 30 Mbps. The setup focuses on three main QoS parameters: audio or video quality, mean opinion score (MOS), voice quality, jitter, and throughput. To monitor the QoS, measurement tools are employed, and data collection is carried out through both active and passive measurement methods, utilising EXFO-FTB test gear and IxChariot. The findings reveal that 88% of the 24 served users received triple-play services, surpassing the standards set by TSP and ETSI in the RoF-WDM-PON downlink system. The approach demonstrates optimal MOS with maintained voice jitter and consistent throughput at a minimum of 18 Mbps, achieving efficient performance and resource utilisation. The results of the trial-based study showed a significant improvement in packet loss, less than 16.67%, and more than 20.9% improvement in throughput compared to the simulation-based benchmark.